ANALISIS FAKTOR-FAKTOR BERPENGARUH TERHADAP MOTIVASI BELAJAR MATERI KELISTRIKAN OTOMOTIF BAGI SISWA KELAS XI SMK YP DELANGGU KLATEN - Joko Rochmadi Raub (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The purpose of this study is to determine factors that influence students’ motivation in vocational automotive electrical major in SMK YP Delanggu Klaten either partially or simultaneously. The study was conducted at SMK YP Delanggu Klaten. The population is all class XI students majoring in automotive, around 128 students, while the sample was 40 students by using purposive sampling techniques. Data collection was through questionnaires. Data analysis techniques used multiple linear regression analysis, by testing the accuracy of the model (F test, the coefficient of determination, the accuracy of parameter estimators and predictors of donation, and the assumption of classical test (test of normality, linearity test, heteroscedasticity test, and test of multicollinearity). The results of this study were: (1) There is a partial influence of student’s interest and knowledge of student’s motivation (0.036 0.05). (2) There is a partial influence on school facilities and students' motivation (0.015 0.05). (3) There is no partial influence in the way teachers impose student’s motivation (0.938 0.05). (4) There are simultaneous influences of the independent variables (interest and knowledge of students, school facilities and infrastructure, and how teachers teach) to the dependent variable (student’s motivation) (F = 17.523).R Square= 59% means that changes in student’s motivation is influenced by variables in the study by 59% in relative terms and the remaining 41% are influenced by variables other than research. Effectively research variables affect student’s motivation to change their interest and knowledge which reaches 28.26%, school facilities and infrastructure reaches 29.88%, and the way teachers teach stands by 0.82%.